2011
DOI: 10.1073/pnas.1104892108
|View full text |Cite
|
Sign up to set email alerts
|

A role for c-Myc in regulating anti-mycobacterial responses

Abstract: c-Myc (Myc) is a well known transcription factor that regulates many essential cellular processes; however, its role in modulating immunity is not known. Here, we showed different species of mycobacteria can induce Myc expression via ERK1/2 and JNK activation. Unexpectedly, the induced Myc is localized in the cytoplasm but not in the nucleus. This induced Myc expression is associated with the induction of TNF-α and IL-6 and with the suppression of intracellular mycobacterial growth. To delineate the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…38 000 molecular weight glycolipoprotein) of mycobacteria to Toll‐like receptor 2 triggers the activation of multiple MAPKs in macrophages . Consistent with our previous studies, our results demonstrated that BCG is able to induce the phosphorylation of JNK, ERK1/2 and p38 MAPK and also translocation of NF‐κB p65 in macrophages. Our results revealed that IL‐17A specifically enhanced BCG‐induced phosphorylation of JNK in macrophages.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…38 000 molecular weight glycolipoprotein) of mycobacteria to Toll‐like receptor 2 triggers the activation of multiple MAPKs in macrophages . Consistent with our previous studies, our results demonstrated that BCG is able to induce the phosphorylation of JNK, ERK1/2 and p38 MAPK and also translocation of NF‐κB p65 in macrophages. Our results revealed that IL‐17A specifically enhanced BCG‐induced phosphorylation of JNK in macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…Signalling pathways of MAPK, including JNK, ERK1/2 and p38 MAPK, are activated in macrophages in response to mycobacterial infection, leading to production of pro‐inflammatory cytokines . The expression of iNOS has also been shown to be regulated by those MAPK pathways .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…c-Myc is a well known downstream target of p38␣ and is known to be important in inflammation and apoptosis. 28,29 In the present study, p38␣ and downstream (c-Myc) signals were both inhibited, confirming that the intratracheal administration of pcDNATM6.2-GW/EmGFP-miR expressing the p38MAPK␣ shRNA vector effectively silenced the p38␣ gene pathway. Our results strongly suggest that inhibition of p38 can improve lung oxygenation, prevent pulmonary edema, ameliorate the histologic changes, and improve lung functioning after transplantation.…”
Section: Discussionsupporting
confidence: 91%
“…The MYB binding sites have been identified in the parsley PAL1 promoter as the sites of fungal elicitor-inducible DNA–protein interactions [54], and the tobacco PR1a promoter [55]. The MYC recognition sites play a critical role in MYC regulation of innate immune responses against mycobacterial infection [56]. Testing these elements from soybeans is now a priority so that we can design the synthetic promoters that are specific and highly induced by pathogens.…”
Section: Discussionmentioning
confidence: 99%